2019
DOI: 10.3390/atmos11010012
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of Fog: The Sensitivity of a Dissipation Phase to Environmental Conditions

Abstract: The sensitivity of fog dissipation to the environmental changes in radiation, liquid-water lapse rate, free tropospheric temperature and relative humidity was studied through numerical experiments designed based on the 2007-Paris Fog observations. In particular, we examine how much of the stratocumulus-thinning mechanism can be extended to the near-surface clouds or fog. When the free troposphere is warmed relative to the reference case, fog-top descends and become denser. Reducing the longwave radiative cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…By simulating several hundred million fog droplets as Lagrangian particles explicitly, this approach could resolve explicitly the diffusional growth of fog droplets, including Köhler theory and gravitational sedimentation representation [8]. Direct numerical simulations have also emerged as a valuable tool in resolving fog on scales in the order of a meter or less [17]. This type of simulation can provide insights into small scale radiation and turbulence interactions and the entrainment on fog evolution and dissipation.…”
Section: Numerical Simulation and Forecastingmentioning
confidence: 99%
“…By simulating several hundred million fog droplets as Lagrangian particles explicitly, this approach could resolve explicitly the diffusional growth of fog droplets, including Köhler theory and gravitational sedimentation representation [8]. Direct numerical simulations have also emerged as a valuable tool in resolving fog on scales in the order of a meter or less [17]. This type of simulation can provide insights into small scale radiation and turbulence interactions and the entrainment on fog evolution and dissipation.…”
Section: Numerical Simulation and Forecastingmentioning
confidence: 99%
“…Droplets can conversely sediment by gravity (Bott, 1991 andDegefie et al, 2015) or turbulent motions (Tav et al, 2018), or evaporate if the supersaturation decreases due to heating or drying of the air mass, e.g., in the case of mixing with the residual dry air (Pilié et al, 1975;Choularton et al, 1981;Gerber, 1991). Additionally, Schwenkel and Maronga (2018) showed that different parametrizations of the activation and condensation processes impact the vertical extent and liquid water path of fog, which strongly affect the fog life cycle (Waersted et al, 2019 andKarimi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of formation and dissipation time of fog relies strongly on ground‐based observational data and localized process studies with numerical models such as large‐eddy simulations. These have been conducted for example in France (e.g., Haeffelin et al ., 2010; Dupont et al ., 2012; Wærsted et al ., 2019; Karimi, 2020) or in the Netherlands (Duynkerke, 1991; Steeneveld and de Bode, 2018) over time‐scales ranging from 6 days (Dupont et al ., 2012) up to 7 years (Wærsted et al ., 2019). According to these studies, radiation fog usually forms during the night through nocturnal cooling (Roach, 1995) and dissipates a few hours after sunrise (Haeffelin et al ., 2010; Bergot, 2016; Steeneveld and de Bode, 2018).…”
Section: Introductionmentioning
confidence: 99%